MEMAHAMKAN AKUNTANSI DENGAN PENALARAN DAN PENDEKATAN SISTEM - Suwardjono Suwardjono (Faculty of Economics and Business, Universitas Gadjah Mada, 1999)
Accounting equation is a useful tool for teaching accounting. However, itsinappropriate use at the beginning of introductory accounting course tends to inhibitstudents' understanding of and reasoning for accounting process. It is difficult forstudents to link the accounting equation as an abstraction of reality with the realworld counterpart it represents. This difficulty is likely to block students' reasoningfor accepting further materials presented to them. To avoid such a dysfunctionalbehavior, an alternative approach that makes more sense should be introduced inaccounting teaching and learning.In this article, to round up the earlier one (Suwardjono, 1999), the authorproposes and describes a system approach to introducing accounting to beginners.This alternative approach brings students to follow logically and conceptually a stepby-step process of developing accounting systems from the simplest or embryonic tothe most sophisticated and computerized ones. In each step, the underlying conceptsand reasoning for refining the systems are discussed along with the teachingstrategies and techniques of explaining them to students. The author believes that thisapproach will give more benefits to students especially to non accounting majorstudents.